Droit d’asile, droit d’expulsion et représentations de l’exilé en Amérique du Sud au xixe siècle - Edward Blumenthal (Diasporas: Circulations, Migrations, Histoire)
This article analyzes the expulsion of exiles in Latin America through the problems of integration and the legal status of exiles. It examines exile integration in terms of local residence and shows that in the 19th century nationality was less important than politics in determining expulsion. Towards the end of the century, two related developments —the codification of asylum law and the creation of legislation to ease the expulsion of foreigners— lead to the separation of the two categories. Asylum became associated with Latin American elites, and expulsion, because nationalized, associated with with European immigrants and criminality.